2022
DOI: 10.1038/s41467-022-33107-0
|View full text |Cite
|
Sign up to set email alerts
|

Holocene seasonal temperature evolution and spatial variability over the Northern Hemisphere landmass

Abstract: The origin of the temperature divergence between Holocene proxy reconstructions and model simulations remains controversial, but it possibly results from potential biases in the seasonality of reconstructions or in the climate sensitivity of models. Here we present an extensive dataset of Holocene seasonal temperatures reconstructed using 1310 pollen records covering the Northern Hemisphere landmass. Our results indicate that both summer and winter temperatures warmed from the early to mid-Holocene (~11–7 ka B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 91 publications
5
29
0
Order By: Relevance
“…As for the mean annual temperature, brGDGTs records from Gushantun and Hani peat in NE China (Zheng et al, 2017, 2018) show a cooling trend during Holocene (Figure 4e and f). In addition, the MAT records based on terrestrial mollusk assemblages from North China (Dong et al, 2022) and based on an extensive pollen dataset from the Northern Hemisphere (Zhang et al, 2022) (Figure 5d) suggested a trend of warming during the early-middle Holocene and cooling during the middle-late Holocene. The brGDGTs records from Gushantun and Hani peat contradicted the records based on mollusk and pollen probably because the brGDGTs records from NE China carried more summer-inferred temperature information rather than the MAT.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As for the mean annual temperature, brGDGTs records from Gushantun and Hani peat in NE China (Zheng et al, 2017, 2018) show a cooling trend during Holocene (Figure 4e and f). In addition, the MAT records based on terrestrial mollusk assemblages from North China (Dong et al, 2022) and based on an extensive pollen dataset from the Northern Hemisphere (Zhang et al, 2022) (Figure 5d) suggested a trend of warming during the early-middle Holocene and cooling during the middle-late Holocene. The brGDGTs records from Gushantun and Hani peat contradicted the records based on mollusk and pollen probably because the brGDGTs records from NE China carried more summer-inferred temperature information rather than the MAT.…”
Section: Resultsmentioning
confidence: 99%
“…(c) BrGDGTs-based mean annual temperature from Gushantun peat (Zheng et al, 2018). (d) Pollen-based annual temperature anomaly based on an extensive pollen dataset (Zhang et al, 2022). (e) Pollen-based mean warmest month (July) temperature sequence from Sihailongwan maar lake (Stebich et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations